BRIC Health Systems and Big Pharma: A Challenge for Health Policy and Management - Victor G. Rodwin; Guilhem Fabre; Rafael F. Ayoub (Kerman University of Medical Sciences, 2018)
BRIC nations - Brazil, Russia, India, and China - represent 40% of the world's population, including a growing aging population and middle class with an increasing prevalence of chronic disease. Their healthcare systems increasingly rely on prescription drugs, but they differ from most other healthcare systems because healthcare expenditures in BRIC nations have exhibited the highest revenue growth rates for pharmaceutical multinational corporations (MNCs), Big Pharma. The response of BRIC nations to Big Pharma presents contrasting cases of how governments manage the tensions posed by rising public expectations and limited resources to satisfy them. Understanding these tensions represents an emerging area of research and an important challenge for all those who work in the field of health policy and management (HPAM).